Pengaruh Independensi, Pengalaman, Due Professinal Care, Pengetahuan Dan Akuntabilitas Terhadap Kualitas Audit (Studi Empiris pada Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Priani, Sri; , Eny Kusumawati. SE,MM.Akt.CA (2016)
The purpose of this research is to knowing and analize empirically the effect of the independence, experience, due professional care, knowladge, and accountability to audit quality, specially on internal auditors working in KAP Surakarta and Yogyakarta . Technique of taking sample used is purposive sampling with the number of samples 35 auditor worked on KAP Surakarta dan Yogyakarta. Analysis of data using multiple linear regression analysis. The result of the research show that independence, experience,and due professional care effect on audit quality. Knowlege and accountabiliy does not effect on audit qulity.